South Africa’s initiative toward an integrated biodiversity data portal - Daly, Brenda; Ranwashe, Fhatani (Frontiers in Ecology and Evolution, 2023)
Researchers and policymakers have called on the South African National Biodiversity Institute (SANBI), in its role as the statutory biodiversity organisation of South Africa, to develop a coordinated and integrated biodiversity informatics hub. While biodiversity information is increasingly available from several providers, there is no platform through which to access comprehensive biodiversity information from a single source. In response, SANBI is developing the Biodiversity Advisor platform, which will integrate geospatial, species and ecosystem data, literature and other data made available by a wide variety of data partners. To do so it has adopted a Service Orientated Architecture, whereby existing, independent biodiversity datasets are integrated. Consolidating such an extensive and varied set of databases, however, introduces some significant operational challenges. Solutions had to be found to address limited infrastructure, the complexity of the system, the lack of taxonomic identifiers, as well as the need for access and attribution. Solutions had to be pragmatic, given limited financial resources and limited capacity for information technology. The emerging outcome is a system that will easily allow users to access most biodiversity data within South Africa from a single, recognised platform.